2023
DOI: 10.2147/jmdh.s431576
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Attitudes Towards Breastfeeding in Terms of Health Safety and Professional Lactation Education: A National Survey of Women

Anna Bednarek,
Iwona Bodys-Cupak,
Adrianna Serwin
et al.

Abstract: Introduction and Objective An important role in building opinions and attitudes regarding breastfeeding by mothers is played by the medical staff taking care of the mother woman expecting a baby. Breastfeeding is a standard in infant nutrition. The knowledge and support of the medical staff can help a woman make the decision to breastfeed. At the same time, it creates conditions for an optimal working environment for medical staff, affecting the quality of care. The aim of the study was identify m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(72 reference statements)
0
0
1
Order By: Relevance
“…The total score of the IIFAS-s scale in our study does not differ from the available evidence, where it can be observed that women present positive attitudes towards exclusive breastfeeding, especially during pregnancy and hospital admission [41,42]. In this study, we did not observe any women who fell into the negative attitude towards breastfeeding category and 67.2% showed a positive attitude towards breastfeeding.…”
Section: Discussioncontrasting
confidence: 72%
“…The total score of the IIFAS-s scale in our study does not differ from the available evidence, where it can be observed that women present positive attitudes towards exclusive breastfeeding, especially during pregnancy and hospital admission [41,42]. In this study, we did not observe any women who fell into the negative attitude towards breastfeeding category and 67.2% showed a positive attitude towards breastfeeding.…”
Section: Discussioncontrasting
confidence: 72%